Pengaruh Penerapan Green Marketing Terhadap Keputusan Menginap di Harris Resort Waterfront Batam - Butar, Risma Arta Juita Butar; Fitri, Nursiah (Civiliza Publishing, 2024)
Currently, environmentally friendly tourism activities have become the most popular trend among tourists worldwide. This has led various tourism elements to innovate by implementing green or environmentally friendly programs. Likewise, the hotel industry, as accommodation for tourists, has adopted various green or environmentally friendly programs to meet tourists' expectations. Designing, promoting, pricing, and distributing products or programs that do not harm the environment is called Green Marketing. Thus, the implementation of green programs by hotels through green marketing, both directly and indirectly, will influence visitors' decisions to stay. This study aims to determine the effect of green marketing on consumer decisions to stay at HARRIS Resort Waterfront Batam. The study covers three dimensions of green marketing, namely green product, green promotion, and green price, using a quantitative research method that includes validity testing, reliability testing, classical assumption testing, hypothesis testing (t-test, F-test, and coefficient of determination analysis). The data analysis technique used is multiple linear regression analysis using the SPSS version 26 program with a sample size of 100 respondents. Data collection techniques were carried out through observation and online questionnaire distribution. Based on the research results, both partially and simultaneously, green marketing (green product, green promotion, and green price) has a positive and significant effect on the decision to stay. The adjusted R square value shows that the influence of green marketing on the decision to stay is 67.9%, while the remaining 32.1% is influenced by other variables not identified in this study, with the most influential dimension being green price. Therefore, this study proves that the application of green marketing has a positive and significant influence on the decision to stay at HARRIS Resort Waterfront Batam.